2013
DOI: 10.1177/0361684313482109
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Female Role Models on Women’s Implicit Science Cognitions

Abstract: Can female science professors benefit women? Women's negative implicit cognitions about science, technology, engineering, and mathematics (STEM) disciplines impact performance in these fields, marking implicit associations as a space for potential change to improve women's participation in STEM. Examining college student science majors (N ¼ 320, 63% women) enrolled in chemistry and engineering courses, our study investigates how meaningful contact with female role models impacts women's implicit cognitions abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
148
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(158 citation statements)
references
References 41 publications
7
148
3
Order By: Relevance
“…This finding is of interest because it is often argued that men are in a wider network of other business owners than women (see Wigren, 2003, for a discussion about male networks in a particular Swedish locality). This finding does not confirm the claim that role models for women are lacking (Latu et al, 2013;Young et al, 2013).…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…This finding is of interest because it is often argued that men are in a wider network of other business owners than women (see Wigren, 2003, for a discussion about male networks in a particular Swedish locality). This finding does not confirm the claim that role models for women are lacking (Latu et al, 2013;Young et al, 2013).…”
Section: Discussioncontrasting
confidence: 82%
“…When certain stereotypes of women are perpetuated, it is difficult to create alternative role models in business (as well as in science) (Latu et al, 2013;Young et al, 2013). As Eccles (1994,2010) found, women often are attracted to activities where they think they can succeed.…”
Section: Women and Men At Workmentioning
confidence: 99%
“…Young et al (2013) found that having positive female role models such as professors or mentors reduced the impact of gendered stereotypes and improved career aspirations. In fact, a number of the women in our study indicated they sought out other female students and mentors, as well as participating in programs through their universities to raise awareness and provide support to women in STEM fields.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of diary entries and attitudinal measures of entering female undergraduates, when STEM was viewed as incompatible with feminine identity, motivation to continue in science careers decreased (London et al 2011). Lack of female role models and social support also decreased motivation for acknowledging one's identity as both a female and a scientist (Young et al 2013).…”
Section: The Gendered Culture Of Stem Graduate Educationmentioning
confidence: 99%
“…The outcome is female attrition along the STEM pathway, such that at the faculty level, only one third across geoscience and life science disciplines are women (18). This further disadvantages female undergraduates, who disproportionately benefit by having women in positions of authority within their discipline; female faculty are more likely to serve as mentors for women (19), and their presence increases female students' confidence in their ability to do science (7), science identities (20), and their performance (21)(22)(23)(24) and persistence (25) in STEM.…”
Section: Introductionmentioning
confidence: 99%